2014
DOI: 10.1111/jocs.12406
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Donor Age on Survival After Heart Transplantation: An Analysis of the United Network for Organ Sharing (UNOS) Registry

Abstract: Compared to donors aged 18-39, age 40 and above is associated with worse adjusted recipient survival in heart transplantation. This survival difference becomes more pronounced as age increases to above 55. However, the survival rate among status IA patients who receive hearts from advanced age donors (≥55) is significantly better compared to similar status IA patients who are managed without transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 12 publications
3
30
1
Order By: Relevance
“…In heart transplantation, two studies suggest that medium-long term patient survival starts to significantly decrease in recipients of transplants from donors aged over 40 (Weber et al, 2014; Gupta et al, 2004), which is consistent with studies measuring the threshold for onset of CAV (30–39 years) (Nagji et al, 2010). The rest of the studies we reviewed confirm the negative effect of donor age in patient survival found by the above two analyses, except for that of Roig et al (2015), in which the increased risk of death associated with the use of transplants from older donors (i.e.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In heart transplantation, two studies suggest that medium-long term patient survival starts to significantly decrease in recipients of transplants from donors aged over 40 (Weber et al, 2014; Gupta et al, 2004), which is consistent with studies measuring the threshold for onset of CAV (30–39 years) (Nagji et al, 2010). The rest of the studies we reviewed confirm the negative effect of donor age in patient survival found by the above two analyses, except for that of Roig et al (2015), in which the increased risk of death associated with the use of transplants from older donors (i.e.…”
Section: Discussionsupporting
confidence: 76%
“…In a 5-year follow-up retrospective study involving 22,960 adult transplant recipients between 2000 and 2012, Weber et al found that after adjusting for different donor and recipient characteristics, heart transplants from donors 40–49 years of age were associated with a slightly increased risk of mortality with respect to those aged 18–39, and that this difference increased progressively in each successive age group (50–55 and >55) (Weber et al, 2014). This is consistent with 40–49 years of age marking the beginning of a curve of decreasing patient survival, but further stratification of the reference group would have been needed to determine whether the effect starts any earlier.…”
Section: Resultsmentioning
confidence: 99%
“…After OHT, the median length of stay was 15 days (25 th , 75 th : 10, 23) for both the ≥70 and 60-69 year old groups, and 14 days (10,21) for the <60 year old group (Table 3). Of patients alive at one year, patients ≥70 years old had lower rates of rejection episodes in the first year (17.8%) compared to patients 60-69 years old (29.5%) and <60 years old (38.2%).…”
Section: Resultsmentioning
confidence: 99%
“…This is a comprehensive database that includes information on all patients who underwent cardiac transplantation in the United States, and the donors whose organs were received by those recipients. [9][10][11] The study population consisted of adult patients (≥18 years old) who underwent a primary or re-do heart transplantation between January 1, 1987 and March 31, 2014. Patients who underwent combined heart-lung transplant were excluded from this analysis.…”
Section: Data Collection and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation